2016
DOI: 10.1038/ncomms12169
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution imaging and computational analysis of haematopoietic cell dynamics in vivo

Abstract: Although we know a great deal about the phenotype and function of haematopoietic stem/progenitor cells, a major challenge has been mapping their dynamic behaviour within living systems. Here we describe a strategy to image cells in vivo with high spatial and temporal resolution, and quantify their interactions using a high-throughput computational approach. Using these tools, and a new Msi2 reporter model, we show that haematopoietic stem/progenitor cells display preferential spatial affinity for contacting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Technical approaches such as PAR-CLIP, which utilizes a photoactivatable nucleoside for more efficient and specific crosslinking, may help provide insight into specific direct targets regulated by MSI proteins(83). In the interim, the Musashi proteins serve as valuable indicators of stem cell reservoirs within tumors, and can be used to gain sophisticated insights into the activity of these populations: for example, a MSI2-based reporter system has recently been useful as a probe for in vivo imaging of HSC dynamics and movement (84). In addition, considering the expression and activity of MSI1 and MSI2 in individual tumors may yield insight into the relationship between transcriptomic signatures and the actual protein signaling networks operative in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Technical approaches such as PAR-CLIP, which utilizes a photoactivatable nucleoside for more efficient and specific crosslinking, may help provide insight into specific direct targets regulated by MSI proteins(83). In the interim, the Musashi proteins serve as valuable indicators of stem cell reservoirs within tumors, and can be used to gain sophisticated insights into the activity of these populations: for example, a MSI2-based reporter system has recently been useful as a probe for in vivo imaging of HSC dynamics and movement (84). In addition, considering the expression and activity of MSI1 and MSI2 in individual tumors may yield insight into the relationship between transcriptomic signatures and the actual protein signaling networks operative in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging was done as described earlier (Fox et al, 2016; Koechlein et al, 2016; Kwon et al, 2015; Zimdahl et al, 2014). Briefly, Actin-dsRed NOD SCID mice (Strain: NOD.Cg- Prkdc scid Tg(CAG-DsRed* MST)1Nagy/KupwJ) were transplanted with CD98 +/+ (denoted as +/+) and CD98 −/− (denoted as −/−) MLL leukemia cells and imaged 7–10 days post-transplant.…”
Section: Methodsmentioning
confidence: 99%
“…Controversies exist about the nature and function of the endosteal (Adams and Scadden, 2006;Calvi et al, 2003;Zhang et al, 2003) and vascular niches (Ding and Morrison, 2013;Ding et al, 2012;Kiel et al, 2005;Pitt et al, 2015;Wang et al, 2007) in the bone marrow, and how exactly the location of HSPCs in these niches may correlate with their function remains to be elucidated. However, emerging evidence suggests that HSCs exist close to arterioles and that hematopoietic 'stress' leads to HSC proliferation and their distribution away from arterioles (Kiel et al, 2005;Koechlein et al, 2016;Kunisaki et al, 2013) (see poster). Using two-photon microscopy in the calvarium of live mice, it was shown that the oxygen tension differed in different regions of the bone marrow cavity with the endosteal niche being less hypoxic than the deep perisinusoidal regions (Spencer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%